Abstract: Towards a risk techniques taxonomy - Peace, Christopher (New Zealand Journal of Health and Safety Practice, 2024)
My research has shown that health and safety practitioners mainly use professional judgement, workshops, and the consequence/likelihood matrix as risk techniques, suggesting a lack of knowledge of the roughly 450 other management techniques. I also found there was a need for a risk technique identification key to help choose between known, documented techniques that might be relevant to an assessment. An identification key is often used in biology to help identify animals and plants but one has not been developed for risk or other management techniques. A “risk canvas” was developed as part of my research and helps risk assessors place 12 techniques in a relevant risk assessment stage but does not provide a structured process to help identify and choose among others that might more relevant or give better results. This presentation will report on work in progress that builds on limited guidance in IEC/ISO31010 to help structure such an identification key that can be used by practitioners to help choose techniques relevant to an assessment. The work showed that the intention to develop a risk techniques identification key should have been titled “Towards a risk techniques taxonomy”. When completed, the taxonomy will help ‘unlock’ access to other techniques. It will help improve the competence of health and safety practitioners and help them become connoisseurs of a wider range of risk techniques. It will give confidence that an assessment has yielded the best available information that management can then use as the weight of evidence for decision making. The taxonomy will also help “mixed methods research”.